Psychological adaptation to extreme environments : Antarctica as a space analogue - Tortello, Camila (2018)
Fil: Tortello, Camila. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina